Novel extensible multilevel inverter based on switched-capacitor structure - Wang, Yaoqiang; Ye, Juncheng; Ku, Ruohan; Wang, Yi; Liang, Jun (JOURNAL OF POWER ELECTRONICS, 2022)
Multilevel inverters (MLIs) play an important role in research on renewable energy conversion. However, in traditional designs, the high-voltage stress of switching devices and the large number of switches limit the wide application of the inverter. To ameliorate these problems, this paper proposes a switched-capacitor multilevel inverter (SCMLI). When compared with traditional MLIs, the proposed SCMLI utilizes a switched-capacitor structure, where the capacitors can achieve voltage self-balancing without auxiliary methods. Thus, it permits changes of the positive and negative polarity of the output level without the need for an H-bridge. In addition, with the augment of the level in the expanded SCMLI structure, the maximum blocking voltage can be kept constant. To show the advantages of the proposed structure, an extensible single dc source five-level SCMLI prototype has been built. Through a comparative analysis with different topologies, this paper also presents the advantages of the proposed topology in terms of the output voltage gain, number of output levels, and voltage stress. Finally, the correctness and feasibility of the proposed inverter are validated by extensive experiments.